Proyecto Fundación Para La Promoción Científica Edbertho Leal Quirós Planetario Astro IN 360 ubicado en Macaravita Santander (2023)
In the following monograph, the design of a planetarium for pedagogical and tourist use for the municipality of Macaravita Santander is proposed, one of the 5 facilities planned by the Edberto Leal Quirós foundation for the development of the municipality